EFEKTIFITAS METODE EFEKTUASI, METODE DESIGN THINKING DAN BISNIS MODEL KANVAS UNTUK MENINGKATKAN KUALITAS KEWIRAUSAHAAN DI TENGAH PANDEMI COVID-19 - Sufatun Nisa; Beni Dwi Komara (PROCEEDING UMSURABAYA, 2022)
ABSTRACT   Indonesian migrant workers need entrepreneurship training so that when they return to their homeland they are empowered in the community. Researchers with a team from the University of Muhammadiyah Gresik and CLC-BJI Taiwan have the task of providing entrepreneurial skills during the COVID-19 pandemic. This study aims to determine whether the method of effectuation, Design Thinking, Business Model Canvas, and bold media used has been effective in improving the entrepreneurial quality of migrant workers in Taiwan. This Participatory Action Research qualitative study involved 70 migrant workers, 1 speaker and 14 facilitators who served as business assistants. The results of this study conclude that the effectuation, design thinking and business model canvas methods used are very effective in increasing the entrepreneurship of Indonesian migrant workers. proven in 16 meetings that migrant workers have been able to innovate new products and create a business model that has been validated. The break out room feature in the Zoom application and the virtual board sharing feature in the Mi application are very effective for migrant workers who can still collaborate to create new product innovations while still complying with social rules due to the COVID-19 pandemic. Keywords                   : Business Model Canvas; Impact of Covid-19; Design Thinking;  Entrepreneurial Effectuation.